2013
DOI: 10.1038/ng.2807
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C modulates TET1 function during somatic cell reprogramming

Abstract: Vitamin C, a micronutrient known for its anti-scurvy activity in humans, promotes the generation of induced pluripotent stem cells (iPSCs) through the activity of histone demethylating dioxygenases. TET hydroxylases are also dioxygenases implicated in active DNA demethylation. Here we report that TET1 either positively or negatively regulates somatic cell reprogramming depending on the absence or presence of vitamin C. TET1 deficiency enhances reprogramming, and its overexpression impairs reprogramming in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
226
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(234 citation statements)
references
References 36 publications
5
226
0
3
Order By: Relevance
“…Previous studies have reported the proliferative and reprogramming effects of vitamin C on stem cells [36][37][38]; however, the molecular mechanism underlying vitamin C-induced stem cell stimulation has not been fully elucidated. Here, we demonstrated that vitamin C induces the proliferation, and vitamin C preconditioning enhanced the hair-regenerative potential of ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the proliferative and reprogramming effects of vitamin C on stem cells [36][37][38]; however, the molecular mechanism underlying vitamin C-induced stem cell stimulation has not been fully elucidated. Here, we demonstrated that vitamin C induces the proliferation, and vitamin C preconditioning enhanced the hair-regenerative potential of ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TET1 overexpression impairs reprogramming (76). Although TET1 in the absence of ascorbate remains functional, the addition of ascorbate is critical for the epithelial-tomesenchymal transition during reprogramming to pluripotency (79).…”
Section: Ascorbatementioning
confidence: 99%
“…This antioxidant promotes TET enzyme-mediated DNA demethylation and acts as a co-factor for histone demethylases JHDM1A/1B in ESCs Chen et al, 2013b;Esteban et al, 2010;Stadtfeld et al, 2012;Wang et al, 2011a). This finding is in line with the emerging importance of metabolic regulation in ESCs (Shyh-Chang et al, 2013a).…”
Section: Oxygen and Nutrients Mediate Epigenetic Dynamicsmentioning
confidence: 99%